REQUIREMENTS FOR LEADING CONSULTANT ON THE DEVELOPMENT OF EDUCATION IN THE RUSSIAN FEDERATION - Trygub, I (Continuing Professional Education: Theory and Practice, 2019)
The article is devoted research of question of preparation of leading consultants on questions development of the system of education. An author expose sleading features, roles of leading consultants on questions development of the system of education and leading tasks, in accordance with directions them professional activity, using experience of Russian Federation. Given the importance of the study of the problem, it can be argued that the problem of training leading consultants on the development of education for the development of the education system in Ukraine becomes important. The problem of formation characteristics leading consultant on the development of the education system is difficult since the significantly affect the progress and results of the expert advisory activities. These characteristics are considered as a professional specialist possible relationship between people that affect the examination and to assume their direct measurement. Preparation of the leading consultants in the development of the education system is being promoted in countries such as Russia, Britain, Germany, Spain and the USA